MARKETING COMMUNICATION STRATEGY OF PROCESSED FISH IN SINABOI VILLAGE SINABOI SUBSDISTRICT ROKAN HILIR DISTRICT - Adli, Arif; Hendri, Ridar; Yulinda, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in January 2017 located in Sinaboi Village District Sinaboi Rokan Hilir Regency. The location of this study was determined purposively, with consideration of Sinaboi Village very potential with processed fish products. The data collection of this research was survey method. According to Arikunto (2012) the information obtained from survey research can be collected from the entire population and can be from only a part of the population. The surveys conducted to all populations are called population surveys / census studies, whereas if data collection is only conducted on a part of the population, it is called a sample survey. From the research there are business characteristics in Sinaboi Village has several processed products ie salted fish, shrimp crackers , And fish nuggets. The total production of all processed fish products is very large reaching 2,280Kg of production using capital of IDR.30.220.000,00 - in one production. The business age at Sinaboi Village varies but the most dominant is more than 5 years. Fish processing business that has been long standing then tend to be open to information so easy to absorb innovations related to marketing. And marketing communications that have been done by fish processors in Sinaboi Village through sales promotion, public relations, direct marketing, and personal sales. The form of marketing communication strategy suitable for salted fish processing in Sinaboi Village is through cooperatives. The strategy for fish nugget and shrimp cracker products is to use mass communication through social media. With mass communication, information will be more quickly accepted widely by all societies.Keywords: strategy, communication, marketing, processed fish